1994
DOI: 10.1002/art.1780370713
|View full text |Cite
|
Sign up to set email alerts
|

Induction of experimental allergic arthritis with outer surface proteins of borrelia burgdorferi

Abstract: Objective. The arthritogenic potential of the cationic outer surface proteins (Osp) from Borrelia burgdorferi was tested in rats.Methods. Water-soluble Osps were prepared by butanol extraction and were administered by intraarticular injection. Tissue injury was assessed by scintigraphy and histology.Results. A mild arthritis was seen in naive rats. Preimmunized animals had more severe, longer lasting bouts of inflammation.Conclusion. The Osps of Borreliu burgdorfen are potent arthritogens in rats. These immuno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
31
0

Year Published

1999
1999
2011
2011

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(33 citation statements)
references
References 35 publications
2
31
0
Order By: Relevance
“…Local inflammation initiated by OSPs, particularly OspA, is a potential major mechanism in the acute phase of Lyme arthritis. In addition to the experimental evidence presented here and previously (13), development of arthritis in humans during B burgdorferi infection is associated with humoral and cellular immune responses to borrelial antigens, including OspA (37)(38)(39). A temporal relationship between the appearance of antibody to OspA and the onset of joint inflammation was previously reported (40).…”
Section: Discussionsupporting
confidence: 75%
See 2 more Smart Citations
“…Local inflammation initiated by OSPs, particularly OspA, is a potential major mechanism in the acute phase of Lyme arthritis. In addition to the experimental evidence presented here and previously (13), development of arthritis in humans during B burgdorferi infection is associated with humoral and cellular immune responses to borrelial antigens, including OspA (37)(38)(39). A temporal relationship between the appearance of antibody to OspA and the onset of joint inflammation was previously reported (40).…”
Section: Discussionsupporting
confidence: 75%
“…Synthetic lipohexapeptide analogs of treponemal and borrelial lipoproteins have been shown to cause acute skin lesions in mice (12). We previously demonstrated that a model of chronic arthritis could be induced in rats with a butanol-extracted, water-soluble OSP complex from B burgdorferi (13). That observation prompted the current set of experiments, which represent the first study in which the pathogenicity of individual recombinant versions of OSPs was directly studied in vivo.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Introduction of B. burgdorferi into skin or joint tissues elicits rapid migration of inflammatory cells, primarily PMN and M into the infected areas (64,78). In infected humans and some animal species, many develop an erythema migrans skin lesion emanating from the inoculation site, that is believed to represent the tissue reaction to inflammatory mediators produced by host inflammatory cells in response to the disseminating spirochetes (2).…”
Section: Il-10mentioning
confidence: 99%
“…These lipoproteins are potent stimulants of proinflammatory products in numerous cell types, including macrophages, endothelial cells, neutrophils, and B lymphocytes (3)(4)(5)(6). Injection of lipoproteins or lipopeptides into joints or skin induces an acute inflammatory infiltrate consisting predominantly of neutrophils (7,8), suggesting that lipoproteins play a major role in inflammatory induction in vivo. The recent identification of TLR2 as the signal-transducing receptor for bacterial lipoproteins leading to nuclear translocation of the inflammatory transcription factor NF-B provides a mechanism for the initiation and modification of inflammatory events associated with Lyme disease (3, 9 -13).…”
mentioning
confidence: 99%